Joint decoding of content-replication codes for flash memories - Qing Li; Huan Chang; Anxiao Jiang; Haratsch, Erich F. (2015 53rd Annual Allerton Conference on Communication, Control, and Computing (Allerton), 2015)
One serious challenge for flash memories is data reliability. In this work, we present the content-replication codeword problem, and it leads to our proposed joint decoder. We focus on joint decoding algorithms and study their theoretical decoding performances. The proposed scheme is novel for flash memories, and we show their reliability can be enhanced by increasing the diversity of error-correcting codes.